Interest in participating in routine exercise at the Dharma Wanita Gymnastics Club, Jambi University Unit - Suhartini, Sugih; Juwita, Putri; Sukendro, Sukendro; Anjanika, Yonifia (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
The number of members of the Dharma Wanita unit at Jambi University in 2024 is 119, but during one of the routine activities of the Dharma Wanita unit at Jambi University, namely routine group gymnastics every Wednesday afternoon which is held at the official residence of the rector of Jambi University, this activity is only attended by 20-30 people each week. . This research aims to find out how interested the Unja DWP is in routine exercise at the Dharma Wanita gymnastics club unit of Jambi University. The method used in this research is distributing questionnaires, where respondents will be given a number of statements and will answer according to their circumstances. The scores obtained from the questionnaire will then be analyzed using qualitative descriptive statistical techniques which are applied in the form of percentages. The total population of all Dharma Wanita Units at Jambi University is 119 members. This number is more than 100 people, so by determining a sample size of 25%, the sample size calculation is 25 members. The results of the research show that the total percentage of DWP interest as a whole answered in the very high category, 8%, totaling 2 members, with the high category 68%, totaling 17 members, with the medium category 8%, totaling 2 members, and the low category 8%, totaling 2 members, with a very low category of 8% with 2 members.